Estimation of Undiagnosed Naegleria fowleri Primary Amebic Meningoencephalitis, United States - Matanock, Almea (Emerg Infect Dis, 2018)
Primary amebic meningoencephalitis is an acute, rare, typically fatal disease. We used epidemiologic risk factors and multiple cause-of-death mortality data to estimate the number of deaths that fit the typical pattern for primary amebic meningoencephalitis; we estimated an annual average of 16 deaths (8 male, 8 female) in the United States.